How Can SEAMEO QITEP in Mathematics Help Indonesian Mathematics Teachers to Help Their Students to be Independent Learners in the Case of Disaster Risk Reduction (DRR)? - Fadjar Shadiq (Southeast Asian Mathematics Education Journal, 2016)
There are a number of disasters threats in Indonesia, such as earthquakes, tsunamis, volcanic eruptions, fires, landslides and floods. When a natural hazard strikes, children are among the most vulnerable population group, especially those attending school in the times of disaster. What people know is more important than what they have when it comes to saving lives and reducing loss. It implies that students should also learn DRR during the teaching and learning of mathematics. This paper reports on a number of studies conducted by SEAMEO QITEP across the years 2012 – 2015 that attempted to improve both teachers and students learningoutcomes.